2009
DOI: 10.5009/gnl.2009.3.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation and Gut Microbes in Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is a highly prevalent disorder that is characterized by chronic abdominal pain and altered bowel habit. The diagnosis of IBS has traditionally been made by matching the complaints of the patient with established clinical criteria, since the underlying pathophysiology was not known. Various new findings have recently been reported in IBS patients that challenge our concept of IBS as a syndrome with no explanation. While the florid inflammation characteristic of inflammatory bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Intestinal infection, on the other hand, can also cause alterations in gut microbiota by a loss of containment of the indigenous colonic microbial community or small intestinal bacterial overgrowth, which can also contribute to visceral afferent sensitization in IBS (Al‐Khatib and Lin, ), possibly also through interference with the intestinal barrier function (Rescigno, ). Further studies are needed to establish the role of these peripheral processes and to which extent they can contribute to alterations in pain perception in IBS.…”
Section: Hyperalgesia Allodynia: a Peripheral Perspectivementioning
confidence: 99%
“…Intestinal infection, on the other hand, can also cause alterations in gut microbiota by a loss of containment of the indigenous colonic microbial community or small intestinal bacterial overgrowth, which can also contribute to visceral afferent sensitization in IBS (Al‐Khatib and Lin, ), possibly also through interference with the intestinal barrier function (Rescigno, ). Further studies are needed to establish the role of these peripheral processes and to which extent they can contribute to alterations in pain perception in IBS.…”
Section: Hyperalgesia Allodynia: a Peripheral Perspectivementioning
confidence: 99%
“…The etiology of IBS is complex and appears to be multi-factorial, including altered gastrointestinal (GI) motility, visceral hypersensitivity, heredity, inflammation, and psycho-social factors. 1,2 Nevertheless, the etiology of IBS remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indicators of immune activation have also been documented in IBS patients without the onset of an acute infection, including alterations in mucosal cytokine production, mast cell activation, increased numbers of enterochromaffin cells and intraepithelial lymphocytes, low‐grade infiltration of T cells in the myenteric plexus with neuronal degeneration, increased fecal concentrations of the antimicrobial peptide beta‐defensin‐2, and increased capsaicin receptor TRPV1‐expressing sensory fibers in rectal biopsies, along with data suggesting a genetic predisposition favoring an increased production of tumor necrosis factor (TNF)‐α (reviewed in Refs. 9 and 21). The putative role of gut microbiota in disturbances of the brain–gut axis in IBS patients is increasingly recognized, and dysbiosis may play a critical role in immune activation and low‐grade inflammation in a proportion of patients 22 …”
Section: Correlational Findings In Patients With Ibsmentioning
confidence: 99%
“…Local inflammation of the intestine may indeed result in systemic immune activation, 12,15,23,24 likely mediated by an increased permeability of the intestinal mucosa 24 . Studies in IBS patients without a history of an infection revealed low‐grade activation of the innate immune system, including systemic increases in inflammatory markers such as TNF‐α, interleukin (IL)‐1β, IL‐6, and IL‐8 9,21 . Importantly, levels of proinflammatory cytokines, analyzed in the serum of IBS patients, have been found to be associated with IBS symptom score 25 .…”
Section: Correlational Findings In Patients With Ibsmentioning
confidence: 99%